Ecological risk assessment of future suitable areas for Piper kadsura under the background of climate change - Li, Shimeng; Li, Yuanxin; Hu, Mingli; Li, Yankun; Yang, Mingrong; Wang, Shi; Yu, Wei; Cheng, Chunsong; Cheng, Qiqing (Frontiers in Plant Science, 2025)
IntroductionPiper kadsura is a well-known medicinal plant that belongs to woody liana, possessing high therapeutic and economic value. The market demand of P. kadsura is huge, but its wild resources are scarce and artificial cultivation methods have not been established, which leads to a situation with strong contradiction and imbalance between supply and demand.MethodsIn this study, 303 sample of distribution data for P. kadsura in China were collected, 33 environmental variables related to terrain, climate and soil were analyzed and the suitable habitats of P. kadsura during various periods were predicted by MaxEnt model and ArcGIS software, aiming to provide a basis for scientific cultivation and effective utilization of resources.ResultsThe results indicated that precipitation and temperature were significant factors in the distribution of P. kadsura. The primary environmental variables influencing the potential distribution of P. kadsura were precipitation during the driest quarter (Bio17), annual precipitation (Bio12), mean diurnal range (Bio2), and annual temperature range (Bio7). Among them, precipitation of driest quarter (Bio17) was the most influential environmental variable for the distribution of P. kadsura with the range between 100.68 and 274.48 mm. The current distribution of P. kadsura is mainly located in the coastal areas of eastern and southern China, especially Guangxi, Guangdong, Zhejiang and Fujian, with a total area of 51.74 × 104 km2. Future climate change of global warming will lead to a reduction in the total suitable areas and high suitable areas under various climate scenarios. Especially in the SSP585 scenario, the total suitable area and the highly suitable area will be significantly reduced by 89.26% and 87.95% compared with the present during the 2090s.DiscussionOverall, these findings can provide useful references for the suitable areas’ determination of wild resources, optimization of artificial cultivation and scientific selection of high quality medicinal materials on P. kadsura.